Advantageous use of SSA technique to observe effects of thickness, antioxidant and oxygen in gamma irradiated low density polyethylene - Pérez, Claudio Javier (2012)
Information obtained from successive self-nucleation and annealing (SSA) technique is analyzed, paying special attention to the observable effects of samples thickness and antioxidant and oxygen concentrations. Molecular structure changes for low density polyethylene (LDPE) samples, irradiated under three different atmospheres for doses between 33 and 222 kGy were analyzed, with emphasis on the changes of longer polymethylene crystallizable lengths. Antioxidant and oxygen concentrations were varied for samples of different thickness to study the effects on degradation. The changes in the molecular structure were followed simultaneously by SSA and Infrared spectroscopy (FTIR) via carbonyl group concentration. Preliminary quantifications of the SSA technique sensitivity are also advanced.